Primary HPV-DNA screening in women under 30 years of age: health technology assessment - Garzón-Olivares, Carmen Doris; Grillo-Ardila, Carlos Fernando; Amaya-Guio, Jairo; Vallejo-Ortega, Maria Teresa; Diaz-Cruz, Luz Amparo; Fernández-Motta, Carolina; Gomez-Motta, Alejandra del Pilar; Barrera, Alina Tatiana; Trujillo-Sánchez, Lina María; Pérez-Moreno, Carlos Humberto; et al. (Revista Colombiana de Obstetricia y Ginecología, 2022)
Background Primary screening with Human Papilloma Virus (HPV) testing was introduced in Colombia in 2014 for individuals between 30 and 65 years of age. When the result is positive, cytology triage is performed for colposcopy referral. The convenience of initiating HPV-DNA testing for screening at 25 years of age is currently a subject of discussion. Therefore, the objective of this health technology assessment (HTA) is to analyze the available evidence regarding safety, efficacy, cost-effectiveness, values and preferences, ethical dilemmas and considerations pertaining to the implementation of the HPV-DNA test as a cervical screening strategy in women under 30 years of age in the Colombian context. Domains to be assessed Clinical efficacy and safety 1. Cumulative rate of cervical intraepithelial neoplasia (CIN) grade 2 or high-er after 2 screening rounds. 2. Cumulative rates of invasive cancer of the uterine cervix after 2 screening rounds. 3. Safety: referral to colposcopy Cost-effectiveness Cost-effectiveness for Colombia. Other domains considered Ethical considerations associated with cervical screening in women under 30 years of age. Organizational and individual considerations. Barriers and facilitators pertaining to the implementation of cervical screening in women under 30 years of age in the Colombian context. Methods Clinical efficacy and safety assessment A systematic literature search of systematic reviews and clinical trials was conducted in MEDLINE, Embase and CENTRAL. The body of evidence was rated using the GRADE approach. An interdisciplinary team was then convened to create a working group to review the retrieved evidence. This led to the discussion and construction of the conclusions following the guidelines of a formal consensus in accordance with the RAND/UCLA methodology. Economic study Systematic literature research of studies that had assessed cost-effectiveness for Colombia. Results Out of the 7,659 references retrieved, 8 studies were included. Clinical outcomes An integrative analysis of 5 randomized clinical trials that met the inclusion critera was performed. Compared with cytology, primary HPV-DNA testing in women under 30 years of age could be associated with a lower frequency of CIN+2 lesions during the first screening round (RR: 1.57; CI: 1.20 to 2.04; low evidence certainty), and a lower incidence of CIN+2 (RR: 0.67; CI: 0.48 to 0.92; low evidence certainty). Moreover, it is associated with a lower frequency of invasive carcinoma at the end of follow-up (RR: 0.19; CI: 0.07 to 0.53; high evidence certainty). Economic results From the financial point of view, the use of HPVDNA testing plus cytology-based triage starting at 25 years of age is perhaps the most cost-effective option for Colombia (incremental cost-effectiveness ratio, COP 8,820,980 in 2013). Other implications Two studies suggest that barriers to implementation attributable to intermediation, public unrest and geographic considerations could be overcome with the use of new screening technologies or strategies. It is important to consider administration and service provision alternatives in order to overcome some acceptability and access barriers. Any cervical screening program must take into consideration ethical principles of nonmaleficence, beneficence, autonomy and equity. Future studies should focus on analyzing new screening techniques with emphasis on the population under 30 years of age. Conclusions The use of HPV-DNA testing as a screening strategy in women under 30 years of age is a potentially efficacious and cost-effective intervention for Colombia. Future studies should focus on analyzing new screening technologies, with emphasis on the population under 30 years of age.